Does Emotional Intelligence Reduce Problematic Social Media Use and Procrastination Through Self-Control Among Generation Z? A Gender-Based Multi-Group Analysis - Sabrina Alfania Subandi; Muhammad Fajar Wahyudi Rahman (Jurnal Manajemen Universitas Bung Hatta, 2026)
Problematic social media use and procrastination have become major behavioural challenges among Generation Z students. However, previous studies have primarily focused on the direct effects of Emotional Intelligence, while the psychological mechanism underlying these relationships remains insufficiently understood. This study aims to examine the effects of emotional intelligence on problematic social media use and procrastination, investigate the mediating role of self-control, and compare the structural relationships between male and female students using Multi-Group Analysis (MGA). A quantitative explanatory approach was employed using data collected from 226 Generation Z respondents through a structured questionnaire. The proposed model was analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and MGA. The findings indicate that emotional intelligence does not significantly reduce problematic social media use but significantly reduces procrastination behaviour and positively influences self-control. Furthermore, self-control significantly reduces both problematic social media use and procrastination behaviour and mediates the relationships between emotional intelligence and both behavioural outcomes. This study contributes to the literature by demonstrating that self-control serves as an underlying psychological mechanism linking emotional intelligence with adaptive digital behaviour among Generation Z. The findings provide practical implications for educational institutions to strengthen emotional intelligence and self-control in promoting digital well-being.